2011
DOI: 10.1128/aac.05500-11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fgd1 and ddn Diversity in Mycobacterium tuberculosis Complex on In Vitro Susceptibility to PA-824

Abstract: PA-824 is a promising drug candidate for the treatment of tuberculosis (TB). It is in phase II clinical trials as part of the first newly designed regimen containing multiple novel antituberculosis drugs (PA-824 in combination with moxifloxacin and pyrazinamide). However, given that the genes involved in resistance against PA-824 are not fully conserved in theMycobacterium tuberculosiscomplex (MTBC), this regimen might not be equally effective against different MTBC genotypes. To investigate this question, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 40 publications
4
39
0
1
Order By: Relevance
“…The orthologs Rv1261c and Rv1558 may be functional analogs of Ddn (6), while other enzymes (Rv1155 and Rv2991) have been found to be structural analogs of FGD1 (3). In a pool of 65 PA-824-susceptible clinical isolates, Feuerriegel et al (35) identified five unique phylogenetic or neutral SNPs in fgd1. Accordingly, the FGD1 model elucidated in this study shows that these phylogenetic SNPs are dispersed outside the F 420 -binding site and are not found in the M. tuberculosis H37Rv resistant mutants selected here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The orthologs Rv1261c and Rv1558 may be functional analogs of Ddn (6), while other enzymes (Rv1155 and Rv2991) have been found to be structural analogs of FGD1 (3). In a pool of 65 PA-824-susceptible clinical isolates, Feuerriegel et al (35) identified five unique phylogenetic or neutral SNPs in fgd1. Accordingly, the FGD1 model elucidated in this study shows that these phylogenetic SNPs are dispersed outside the F 420 -binding site and are not found in the M. tuberculosis H37Rv resistant mutants selected here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the related drug PA-824, delamanid is a prodrug requiring activation by the mycobacterial F420 system, including the nitroreductase Ddn (Rv3547) (8)(9)(10). Delamanid resistance is thought to arise from mutations in the mycobacterial F420 genes (ddn, fgd1, fbiA, fbiB, and fbiC) associated with the prodrug's activation (8,11). The spontaneous rate of delamanid resistance has been reported to be as high as 6.44 ϫ 10 Ϫ6 to 4.19 ϫ 10 Ϫ5 , emphasizing the need to protect delamanid with other active anti-TB drugs during therapy (9).…”
mentioning
confidence: 99%
“…Mutations have been identified in fgd1 and ddn [57,62,63], with cross-resistance to 5-nitrothiophenes (a tuberculostatic compound) [64] as well as delamanid [53]. With minimal inhibitory concentration (MIC) around 0.15-0.3 μg·mL −1 [58,63], the activity of PA-824 is comparable to a combination of isoniazid and rifampicin in the continuation phase of a murine drug model [61].…”
Section: Pa-824 ( Pretomanid)mentioning
confidence: 97%